Characteristics and challenges of open-water swimming performance: A review - Baldassarre, R.; Bonifazi, M.; Zamparo, P.; Piacentini, M. F. (International Journal of Sports Physiology and Performance, 2017)
Context: Although the popularity of open-water swimming (OWS) events has significantly increased in the last decades, specific studies regarding performance of elite or age-group athletes in these events are scarce. Purpose: To analyze the existing literature on OWS. Methods: Relevant literature was located via computer-generated citations. During August 2016, online computer searches on PubMed and Scopus databases were conducted to locate published research. Results: The number of participants in ultraendurance swimming events has substantially increased in the last 10 y. In elite athletes there is a higher overall competitive level of women than of men. The body composition of female athletes (different percentage and distribution of fat tissue) shows several advantages (more buoyancy and less drag) in aquatic conditions that determine the small difference between males and females. The main physiological characteristics of open-water swimmers (OW swimmers) are the ability to swim at high percentage of V.O 2 max V.O2max (80-90%) for many hours. Furthermore, to sustain high velocity for many hours, endurance swimmers need a high propelling efficiency and a low energy cost. Conclusion: Open-water races may be characterized by extreme environmental conditions (water temperature, tides, currents, and waves) that have an overall impact on performance, influencing tactics and pacing. Future studies are needed to study OWS in both training and competition.